Burn-in : a novel of the real robotic revolution - Singer, P. W. (Peter Warren); Cole, August (Houghton Mifflin Harcourt, 2020)
"America is on the brink of a revolution, one both technological and political. The science fiction of AI and robotics has finally come true, but millions are angry and fearful that the future has left them behind. After narrowly stopping a bombing at Washington's Union Station, FBI Special Agent Lara Keegan receives a new assignment: to field-test an advanced police robot. As a series of shocking catastrophes unfolds, the two find themselves investigating a conspiracy whose mastermind is using cutting-edge tech to rip the nation apart. To stop this new breed of terrorist, their only hope is to forge a new type of partnership."--Provided by publisher.